Carry trade - Òscar Jordà (University of California, Department of Economics, 2010)
It does not take much sophistication for a speculator to generate risk-adjusted positive returns with the carry trade. A number of obvious improvements (such as optimally designed portfolios, strategies that permit the speculator to remain in a cash position when expected returns are small or uncertain, and others not considered here) would only improve the speculator's returns further. That this is so poses a challenge to conventional notions of market efficiency and long-standing puzzles in international finance. The carry trade is a risky investment but its positive returns are hard to justify on the basis of the investor's tolerance for exposure or how returns correlate with a wide range of alternative risk factors.
Keywords: 330